(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article presents a simple and environmentally friendly method for the production of flexible, ultra-lightweight and hydrophobic cellulose aerogels (CA), based on a process of chemical crosslinking, lyophilization of a cellulose solution and subsequent hydrophobic modification with methyl trichlorosilane (MTCS) (heat treatment). chemical vapor deposition CVD). The resulting cellulose aerogels are bonded to each other and have a very large porous structure characterized by different pore sizes due to different concentrations of the initial solution. In addition, the cellulose aerogels were extremely light (only 0.027 g/cm3), but they showed improved mechanical properties when the compressive strength was 1.10-3.85 MPa. After silanization, the MTCS modified cellulose aerogels exhibited constant hydrophobicity with an average contact angle of 1410 with water and retained 1310 even after 5 days.